FORMAL ANALYSIS OF ISOCHRON CONSTRUCTION IN 40AR/ 39AR GEOCHRONOLOGY - Brandt S.B.; Rasskazov S.V.; Brandt I.S.; Ivanov A.V. (My University, 2004)
Formal analysis of argon isotope distribution in minerals in terms of Fick's and Arrhenius laws demonstrated that the linear dependency 36Ar/40Ar-39Ar/40Ar is a true isochron with all the corresponding regressions and extrapolations only when the activation energy of diffusion of the radiogenic isotope 40Arrad is equal to that of the nucleogenic isotope 39Ar, and somewhat higher than the activation energy of diffusion of the contaminating component (40Ar, 36Ar)c. The disturbances of the kinetic parameters of argon isotopes (different activation energies of radiogenic and nucleogenic argon) or radiogenic argon losses during geologic history produce a curved distribution and scatter in the Ar-Ar coordinates leading to erroneous interpretations of ages and 36Ar/40Ar values of the contaminating component.